Visual Basic 2010 programmer's reference - Stephens, Rod 1961- (Wrox programmer to programmer, 2010)
Describes the concepts of programming with Visual Basic 2010, covering such topics as Windows forms, program and module structure, data types, operators, subroutines and functions, error handling, LINQ, UAC security, OOP concepts, and graphics